2012
DOI: 10.5402/2012/253742
|View full text |Cite
|
Sign up to set email alerts
|

Design of High-Speed Adders for Efficient Digital Design Blocks

Abstract: The core of every microprocessor and digital signal processor is its data path. The heart of data-path and addressing units in turn are arithmetic units which include adders. Parallel-prefix adders offer a highly efficient solution to the binary addition problem and are well suited for VLSI implementations. This paper involves the design and comparison of high-speed, parallel-prefix adders such as Kogge-Stone, Brent-Kung, Sklansky, and Kogge-Stone Ling adders. It is found that Kogge-Stone Ling adder performs m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…KSA is a parallel prefix form of carry look-ahead adder. It generates the carry signals in O(log 2 N) time, and is thus widely considered as the fastest adder design possible [11].…”
Section: Vedic Multipliermentioning
confidence: 99%
“…KSA is a parallel prefix form of carry look-ahead adder. It generates the carry signals in O(log 2 N) time, and is thus widely considered as the fastest adder design possible [11].…”
Section: Vedic Multipliermentioning
confidence: 99%
“…The parallel prefix structures are used in high‐performance applications because the time delay is logarithmically proportional to the adder bit‐size. Parallel prefix adders offer a highly efficient solution to the addition operation and are well suited for ASIC implementations . These adders consist of three stages: generate/propagate computations , prefix , and final summation .…”
Section: Proposed Hardware Structures Of the Simon And Speck Block CImentioning
confidence: 99%
“…Therefore, here, we use this adder for implementing the modular adder in the SPECK block cipher. In Yagain et al, the authors presented the design and comparison of high‐speed, parallel prefix adders such as Kogge‐Stone, Brent‐Kung, Sklansky, and Kogge‐Stone Ling adders. The implementation and comparison are performed using both CMOS logic and transmission gate logic.…”
Section: Proposed Hardware Structures Of the Simon And Speck Block CImentioning
confidence: 99%
“…In [12], the development and comparison of high-speed supplementary elements of the prefix, such as Kogge-Stone, Brent-Kung, Sklansky and Ling, are presented. It is revealed that the structure of Kogge-Stone-Ling is more effective than other prefix structures.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%